The Correlation between Socioeconomic Status and Reading Proficiency of English Education Students - Oktariani, Meriska; Warna, Dewi; Ilma, Ridha (Journal of English Language and Education, 2025)
Socioeconomic status (SES) is often assumed to influence students’ academic achievement, including reading proficiency. However, students from higher socioeconomic backgrounds may still struggle with reading performance. This study aimed to examine the correlation between SES and reading proficiency among sixth-semester students in the English Education Study Program at UIN Raden Fatah Palembang. A quantitative correlational method was employed, using an SES questionnaire and a TOEFL-based reading proficiency test. The results showed that most participants came from middle-class families, yet their reading proficiency was generally low. Statistical analysis revealed no significant correlation between SES and reading proficiency (r = -0.18, p = 0.857). These findings suggest that SES alone may not adequately predict students’ reading performance, highlighting the importance of other factors such as reading motivation, metacognitive awareness, and academic support.